Complete Nucleotide Sequences of Two VIM-1-Encoding Plasmids from Klebsiella pneumoniae and Leclercia adecarboxylata Isolates of Czech Origin - Papousek, Ivo (Antimicrob Agents Chemother, 2017)
Two multidrug resistance (MDR) plasmids, carrying the VIM-1-encoding integron In110, were characterized. Plasmid pLec-476cz (311,758 bp), from a Leclercia adecarboxylata isolate, consisted of an IncHI1 backbone, a MDR region, and two accessory elements. Plasmid pKpn-431cz (142,876 bp), from a sequence type 323 (ST323) Klebsiella pneumoniae isolate, comprised IncFII(Y)-derived and pKPN3-like sequences and a mosaic region. A 40,400-bp sequence of pKpn-431cz was identical to the MDR region of pLec-476cz, indicating the en bloc acquisition of the VIM-1-encoding region from one plasmid by the other.